A Novel DWT Domain Watermarking Scheme Based On a Discrete-Time Chaotic System. Issue 33 (2018) - Hannoun, Katia; Hamiche, Hamid; Lahdir, Mourad; Laghrouche, Mourad; Kassim, Sarah
Abstract: In this paper, we present a novel watermarking scheme in the Discrete Wavelet Transform (DWT) domain based on a discrete-time chaotic system. A modified Hénon map and a discrete step-by-step observer are, respectively, considered as transmitter and receiver of the chaotic transmission scheme, leading to an exact synchronization and therefore an exact recovery of the system states. The secret keys of the transmission scheme are the transmitter parameters. The said modified Hénon map is used to encrypt an image, inserted by inclusion method in the chaotic discrete-time system's dynamics, to then use the resulting cyphered image as a watermark to a host image. This host image is watermarked by a DWT domain watermarking function. After the extraction process, the recovered watermark is then sent through the previous chaotic channel to decrypt it. Simulation results are presented to highlight the feasibility and robustness of the proposed method.